2017
DOI: 10.1007/s00464-017-5619-5
|View full text |Cite
|
Sign up to set email alerts
|

Per oral endoscopic pyloromyotomy for refractory gastroparesis: initial results from a single institution

Abstract: POP is a safe and feasible endoscopic intervention for medical refractory gastroparesis. Additional follow-up is required to determine the long-term success of this approach in alleviating gastroparesis symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 21 publications
1
102
0
1
Order By: Relevance
“…Initially a submucosal bleb is raised with an injection of a solution containing methylene blue approximately 4 cm proximal to the pylorus along the lesser curvature of the stomach. 36 Some authors have reported a greater curve approach but we find that this induces more retroflexion of the endoscope. Our group prefers to use a triangle tip knife for the initial mucosotomy, submucosal dissection, and muscular division of the pylorus.…”
Section: Surgical Techniquementioning
confidence: 49%
See 4 more Smart Citations
“…Initially a submucosal bleb is raised with an injection of a solution containing methylene blue approximately 4 cm proximal to the pylorus along the lesser curvature of the stomach. 36 Some authors have reported a greater curve approach but we find that this induces more retroflexion of the endoscope. Our group prefers to use a triangle tip knife for the initial mucosotomy, submucosal dissection, and muscular division of the pylorus.…”
Section: Surgical Techniquementioning
confidence: 49%
“…Initially described in 2013, the procedures is increasing in popularity and data reported in the literature. 34…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations